2011
DOI: 10.1111/j.1469-0691.2010.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prolonged antimicrobial chemotherapy for brucellar spondylodiscitis

Abstract: The standard treatment of brucellar spondylitis with a combination of two antibiotics for 6-12 weeks is associated with high rates of treatment failure and relapse. The present study aimed to assess the safety and efficacy of a treatment strategy based on the prolonged administration of a triple combination of suitable antibiotics. Eighteen patients with brucellar spondylitis were treated with a combination of at least three suitable antibiotics (doxycycline, rifampin, plus intramuscular streptomycin or cotrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
(41 reference statements)
4
21
0
7
Order By: Relevance
“…The remaining four cases (three with paraverbral abscesses and one with multiple levels of vertebral involvement) required antibiotic treatment due to persistence of clinical signs and symptoms which were not detected after six months of treatment. Our findings and the results of other researchers showed that the longer duration of therapy, regardless of type of treatment regimen, is associated with a lower failure rate [12,15].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The remaining four cases (three with paraverbral abscesses and one with multiple levels of vertebral involvement) required antibiotic treatment due to persistence of clinical signs and symptoms which were not detected after six months of treatment. Our findings and the results of other researchers showed that the longer duration of therapy, regardless of type of treatment regimen, is associated with a lower failure rate [12,15].…”
Section: Discussionsupporting
confidence: 78%
“…However, using a triple combination of antibiotics (streptomycin 1 g/day for 15 days and doxycycline 100 mg every 12 hours orally for 45 days plus rifampicin 15 mg/kg per day in a single morning dose orally for 45 days) a small series of cases had higher cure rates [11]. In a recent study in Greece, Ioannou et al treated 18 cases of brucellar spondylodiskitis for between 6 and 18 months using a triple antibiotic combination and, based on clinical, radiological and serologic responses, no relapses were detected [12]. So far, consensus on the optimal regimen of antibiotics to be used and duration of treatment has not been reached, making the treatment of spinal brucellosis controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Questões como, qual o melhor esquema de antibioterapia, qual a duração do tratamento e qual o papel da cirurgia permanecem sem uma resposta definitiva. 22 A maioria dos estudos sugere uma melhor resposta dos regimes de doxiciclina/aminoglicosídeo (estreptomicina e gentamicina) relativamente aos de doxiciclina/rifampicina, 9,13,23 que no entanto tem a vantagem de ser uma associação de administração por via oral. 24 Segundo uma meta-análise, que avaliou oito estudos relevantes, os resultados estão relacionados com a duração do tratamento e não com o tipo de regime terapêutico usado.…”
Section: Discussionunclassified
“…Um estudo prospectivo de EB, no qual foi avaliada a eficá-cia de uma terapêutica superior a seis meses, apresentou taxas de sucesso de 100,0%, sem recidivas, sequelas graves ou mortalidade. 22 Neste estudo, as associações de doxiciclina com rifampicina ou estreptomicina foram as mais frequentes, sendo os regimes com estreptomicina os mais usados nos últimos anos do estudo. O esquema triplo de antibioterapia foi opção em apenas 7,4% dos doentes.…”
Section: Discussionunclassified
“…Tedavide kullanılabilecek en uygun antibiyotik seçenekleri, tedavinin süresi ve tedaviye yanıtın nasıl değerlendirilebileceği gibi konular hala net değildir. Verilen tedavi süresinin ortalama 12 ay gibi uzun olduğu bir çalışmada (en kısa 6 ay, en uzun 18 ay), tedaviyle % 100 başarı sağlanmış ve relaps, ağır sekel ve mortalite gibi komplikasyonlara rastlanmamıştır (14).…”
Section: Discussionunclassified